Utilization Of Cloud Accounting During the Covid-19 Pandemic for Owners and Customers in Cooperative Business - Mohhamd Ghofirin; Niken Savitri Primasari (CV ODIS, 2022)
All organizations including the Republic of Indonesia Employee Cooperative (KPRI) business unit are dealing with changes in the industrial era 4.0 and covid-19. The implication of both is the use of digital technology for management activities, including financial management. The Surabaya City Government (Pemkot) KPRI is unique compared to other KPRIs in that it is the only KPRI in this city that uses a cloud accounting system and the beginning of its implementation took place in the Covid-19 era. This study aims to explore the use of cloud accounting in the perspective of cooperative members who have multiple roles in the organization. This research was conducted with a qualitative approach with four types of application users as resource persons. The results showed that the application utilization was driven more by hedonic motivational factors and price values. In addition, the use of the application is more for optimizing members as owners and not as cooperative customers.